Five-year experience of continuous ambulatory peritoneal dialysis in children: a single center experience in a developing country (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND The pediatric peritoneal dialysis (PD) program in Cipto Mangunkusumo Hospital, Indonesia was started in 2014. However, there has been no published data on the patients' outcome. This study was aimed to report the characteristics and outcomes of a continuous ambulatory peritoneal dialysis (CAPD) program for children. METHODS This retrospective study was conducted in Cipto Mangunkusumo Hospital as a national referral hospital. Data were collected from medical records of patients aged ≤18 years with end-stage renal disease who underwent CAPD in 2014–2019. The baseline characteristics, PD-related infection rate, as well as patient and technique survivals were analyzed. RESULTS Out of 60 patients who underwent CAPD, 36 (60%) were boys on the age range of 4 months–18 years. The mean follow-up duration was 12 (95% confidence interval [CI] = 9.4–15.3) months. The number of PD related infections increased along with the growing number of patients on CAPD. The peritonitis rate was 0.42 episodes per year at risk, and the most common etiology was alpha-hemolytic Streptococcus (5/24, [20.8%]). The 1- and 3-year technique survival rates were 60.3% (95% CI = 44.5–72.9) and 43.9% (95% CI = 23.2–62.9). The 1- and 3-year patient survival rates were 69.6% (95% CI = 52.5–81.5) and 58% (95% CI = 31.2–77.5). CONCLUSIONS In this unit, CAPD could be performed in children as young as 4 months of age. The peritonitis rate was relatively low which was likely caused by skin-derived microorganisms. Both technique survival and patient survival were also relatively low.